How does reputation economy engagement work to develop financial and economic activity? - Safiullin, Marat Rashitovich; Kurbangalieva, Dinara Lenarovna; Elshin, Leonid Alekseevich (Opción, 2019)
The article attempts to assess the impact of the reputation economy on the organization on the basis of open data on the reaction and actions of customers in search engines and social networks. Furthermore, there is a correlation and regression analysis between indicators and sales volume. In result, the ability to develop and adapt sales systems from new informational conditions becomes the main tool in the fight for consumers on the Internet. In conclusion, the shares of involvement in the social networks VK and Instagram for Hyundai, Volkswagen and Toyota are the most evenly distributed, while sales are evenly growing.